Efektivitas Perendaman Tangan Kaki dengan Air dan Pengolesan Campuran VCO dan Olive Oil dalam Mengatasi Efek Samping Kemoterapi (Palmar-Plantar Erythorodysesthesia) pada Pasien Kanker Kolon di Murni Teguh Memorial Hospital - Seriga Banjarnahor; Harsudianto Silaen (Jurnal Riset Hesti Medan, 2019)
Patients with colon cancer undergoing chemotherapy at the Pure Teguh Memorial Hospital both inpatient and outpatient experience many Palmar-Plantar Erythrodysesthesia. Palmar-Plantar Erythrodysesthesia incident that occurs in colon cancer patients due to side effects of chemotherapy. The high incidence of Plamr-Plantar Erythrodysesthesia in colon cancer patients is related to the lack of immersion of the feet with water and the application of a misture of VCO and olive oil. This type of research is a quasy experimental study of post test only non eguivalent control group design that aims to determine the effectiveness of soaking the foot with water and applying a mixture of VCO and Olive Oil in overcoming the side effects of chemotherapy (Palmar-Plantar Erythrodysesthesia) in colon cancer patients in Pure Teguh Memorial Hospital.The population in this study were all colon cancer patients who were undergoing chemotherapy in the Murni Teguh Memorial hospital chemotherapy center as many as 90 patients and a sample of 90 patients consisting of 45 people in the intervention group and 45 in the control group). Data were analyzed with chi square test. The results of the study are the effectiveness of foot immersion soaking with water and the application of a mixture of VCO and olive oil  to overcome the side effects of chemotherapy (Palmar-Plantar Erythrodysesthesia) in colon cancer patients at Murni Teguh Memorial Hospital.As a suggestion in this study, it is expected that immersion of foot hands with water and the application of a mixture of VCO and olive oil  to reduce Palmar-Plantar Erythrodysesthesia in colon cancer patients at Murni Teguh Memorial Hospital and for patients should immerse foot hands with water and basting mixture of VCO olive oil data to reduce the incidence of Palmar-Plantar Erythrodysesthesia.